1992
DOI: 10.1128/iai.60.3.885-891.1992
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of serum, tear, and corneal antibody responses in resistant and susceptible mice intracorneally infected with Pseudomonas aeruginosa

Abstract: The studies described here are aimed at determining the kinetics of antibody responses specific to Pseudomonas aeruginosa ATCC 19660 in sera, tears, and corneas of naturally resistant DBAI2 mice and susceptible C57BL16 mice after intracorneal infection. Immunoglobulin (IgG) and IgM responses in sera were significantly greater in DBA/i2 mice for the first 2 weeks postinfection. Little or no IgA was detected in the sera of mice from either strain. IgG was the predominant immunoglobulin class present in the corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 19 publications
1
5
1
Order By: Relevance
“…It was reported that after topical challenge with Pseudomonas aeruginosa, IgA was secreted locally into tears without systemic production of IgA. 17 Our data, however, that the production of IgA in splenic cells culture was also increased (Fig. 5) implied that IgA could be produced in central lymphoid organs (e.g., spleen in this case) and during corneal infection with C. albicans.…”
Section: Discussioncontrasting
confidence: 42%
“…It was reported that after topical challenge with Pseudomonas aeruginosa, IgA was secreted locally into tears without systemic production of IgA. 17 Our data, however, that the production of IgA in splenic cells culture was also increased (Fig. 5) implied that IgA could be produced in central lymphoid organs (e.g., spleen in this case) and during corneal infection with C. albicans.…”
Section: Discussioncontrasting
confidence: 42%
“…Data indicated that HCEC‐derived TSLP induced a higher level of IgG but did not change the expression of IgA in the supernatant of PBMC. Preston et al also reported that IgA was not found in the serum of mouse corneas infected with Pseudomonas aeruginosa . We surmised that this phenomenon may be related to IL‐4, a potent IgG class switch factor .…”
Section: Discussionsupporting
confidence: 90%
“…Immune response to infection. Previous works have established the pattern of immune responses to P. aeruginosa antigens during corneal infection with strain 19660 (20,22,23). In this study, we sought to determine whether P. aeruginosaspecific serum IgG could be elicited after infection with lowlevel challenge doses.…”
Section: Resultsmentioning
confidence: 99%
“…In this model, scratches are made on the corneas of mice anesthetized with inhalants such as ether, and the challenge strain of P. aeruginosa is applied in a small volume (5 l). However, only a few strains of P. aeruginosa have been reported to be pathogenic under these conditions, and inocula of 10 7 to 10 8 CFU are needed to initiate infection (1,2,11,15,20,22,23). The limited number of virulent strains and the need for high-challenge inocula has restricted the use of this model in the evaluation of microbial and host factors involved in the pathogenesis of P. aeruginosa corneal infections.…”
mentioning
confidence: 99%